Ashley Bell : Ashley Bell #1 - Koontz, Dean R., 1945- (Dean Ray); Jackson, Suzy; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2015)
At twenty-two, Bibi Blair's doctors tell her that she's dying. Two days later, she's impossibly cured. Fierce, funny, dauntless, she becomes obsessed with the idea that she was spared because she is meant to save someone else. Someone named Ashley Bell. This proves to be a dangerous idea. Searching for Ashley Bell, ricocheting through a Southern California landscape that proves strange and malevolent in the extreme, Bibi is plunged into a world of crime and conspiracy, following a trail of mysteries that become more sinister and tangled with every twisting turn.
Title from container.
Compact disc.
In container (17 cm.).
Narrated by Suzy Jackson.
Keywords: Young women -- California -- Fiction; Suspense fiction; Mystery fiction; Audiobooks